Analisis Faktor-Faktor yang Memengaruhi Intensitas Penggunaan Pembayaran Digital QRIS pada Civitas Akademik - Chandra, Sayyidatul Aisyah Abigail Alhabi; Sholahudin, Muhammad Sa’id; Adjie, Raditya Nuswantoro; Widyastuti, Umi; Kurnianti, Destria (Universitas Pahlawan Tuanku Tambusai, 2025)
In Indonesia, especially among people who actively use technology, including academics, the Quick Response Code Indonesian Standard (QRIS) has developed significantly to assist digital transactions. Using the Technology Acceptance Model (TAM) framework, this study aims to study the factors that influence the use of QRIS among academics. The two main variables prioritized by TAM are perceptions of the usefulness of QRIS and ease of use, each of which is considered to have a significant influence on technology acceptance. This study utilized a survey method to collect data from university students who use QRIS as an official payment method. The results showed that the usefulness and ease of use of QRIS have a significant influence on the amount used in the academic community. In addition, it has been shown that additional reasons, such as perceived security and ease of use of QRIS technology, greatly influence the decision to use it. According to data analysis, perceptions of the benefits of QRIS in facilitating transactions and ease of use have a significant influence on increasing the frequency of use. These factors show how important TAM is to implementing QRIS in the world of education. The results of the study indicate that digital payment service managers must consider factors of convenience and better security. This will allow QRIS to become more popular in the academic world.